STATE, PRODUCTIVITY, MERCHANTABILITY, AND ASSORTMENT STRUCTURE OF NATURAL OAK STANDS IN SUMY REGION - Lunachevskyy, L. S.; Tarnopilskyy, P. B.; Rumyantsev, M. G.; Chygrynets, V. P. (Forestry and Forest Melioration, 2018)
Introduction Assessment of the forest condition, taking into account the influence of various anthropogenic and climatic factors, is required for predicting their weakening as well as for the development of forest management to improve the stability and productivity of the forest stands. The main task of forestry is to increase productivity and improve the quality of forest plantations. Yield and quality of oak stand largely depend on forest management methods. In the lowland forests of Ukraine, the traditional methods of management with a focus on clear-cutting and the subsequent shoot reafforestation or creation of forest cultures didn’t allow implementing the idea of expanded reproduction of high-yielding and resistant oak stands. These trends lead to the depletion of the gene pool, activate the processes of weakening and reduce the potential ability to self-reproduction. Materials and Methods The research was conducted in natural oak stands of VIII–XIV age classes in “Sumy Forest Economy” in fresh fertile conditions using standard forestry, forest ecology, and forest inventory methods. To identify and compare the inventory parameters and health conditions of the stands and to investigate the features of their growth, sample plots were established. The comparative analysis of the characteristics and growth of natural oak stands of different ages and species composition was made. Results During the research, it was found that almost all research areas of plantations are noted as weakened (sample plots 2, 4) and very weakened (sample plots 1, 3) (the health condition index was ranged from II,1 to II,7). The mature stands only, with the share of economically valuable species in the composition of 7 units (sample plot 6) and 8 units (sample plot 5) were described as healthy ones. The resistance of the stands is markedly affected by their composition. Forest stands with greater participation of oak and ash in the composition were characterized by better health as compared to the stands where their share is negligible. Thus, the index of the sanitary condition of the oak was within I,4–III,0; of ash, I,0–I,9, and for related species, it was within І,0–ІІІ,1. The worst oak health conditions (III,0) was marked at the sample plot where the share of oak trees in the composition was only 3 units. Such a low index of sanitary condition with the little share of dead wood (8.1%) in an oak plantation indicates weakening not only dwarfed and stunted oaks but the dominant trees, too. The total yield of wood of economically valuable tree species depends on the share of oak and ash in the composition of the stand. This pattern is well evident in the analysis of the volumes in sample plots 2, 3, and 4 where the stands are about the same age but different in composition. In the sample plot 2, the share of economically valuable species is 6 units; in the sample plot 3 it is 8 units; in the sample plot 4, it amounts 6 units. The largest total yield of oak and ash was found in the sample plot 3 – 338 m3 ? ha -1, while the yield in the sample plots 2 and 4 is much lower, 233 m3 ? ha-1 and 242 m3 ? ha-1, respectively; it is almost 30 % less than in the sample plot 3. There is the same pattern for the merchantable wood volume: it is the largest in the sample plot 3 – 184 m3 ? ha-1. The merchantable wood volume in sample plots 2 and 4 is 115 m3 ? ha-1 and 118 m3 ? ha-1, respectively, which is almost 36 % less than in the sample plot 3. Conclusions Oak stands of vegetative origin in fresh fertile Left-bank Forest-Steppe is mostly weakened and very weakened and require timely and proper cleaning cutting and selection and sanitary felling that will improve their biological stability. The presence of oak trees of natural seed origin in the stand will improve the health condition and the productivity of the forests and will provide a maximum yield of merchantable wood at the age of maturity.